Hyperferritinemic sepsis: an opportunity for earlier diagnosis and intervention? - E. Scott Halstead; Surender Rajasekaran; Julie C. Fitzgerald; Scott L. Weiss (Frontiers Media S.A., 2016)
We describe a case of an infant with HSV meningitis and septic shock who demonstrated a remarkably high serum ferritin level. Aggressive pediatric intensive care and the administration of high dose glucocorticoids were not able to reverse the multiple organ dysfunctions. Subsequent autopsy identified the presence of hemophagocytosis, thus the patient fulfilled hemophagocytic lymphohistiocytosis (HLH) criteria post-mortem. This case highlights that serum ferritin may be in important early indicator of mortality in sepsis due to a cytokine storm similar to macrophage activation syndrome (MAS) and HLH.